PENGARUH PENGGUNAAN PACLOBUTRAZOL, KNO3 DAN ETEFON PADA PEMACUAN PEMBUNGAAN TANAMAN MANGGIS (Garcinia mangostana L.) - Syafitri, Novalia; Karyanto, Agus; Rugayah, Rugayah; Widagdo, Setyo (JURNAL AGROTROPIKA, 2020)
Mangosteen (Garcinia mangostana L.) is a tropical plant that bears seasonal fruit and is one of Indonesia's leading export commodity.  Mangosteen production in Indonesia is still low and not continuous, because there are several factors that influence it.  One of them is the character of biennial bearing in mangosteen one year produce high fruit load followed by a next year of very low production.  Therefore it is necessary to induce off season mangosteen flowering.  This study aims to determine: (1) the effect of Paklobutrazol on the flowering of mangosteen plants, (2) the effect of adding KNO3 and Etefon on the acceleration of mangosteen flowering.  This research was conducted in Mulangmaya Village, Kota Agung Timur District, Tanggamus, Lampung.  Regency at an altitude of 250 m above sea level from September 2018 to April 2019.  This research used a Randomized Block Design (RBD) with a single factor consisting of 3 treatments, namely P1 ( manure 10 kg/plant + NPK Nitrophonska 1 kg/plant, P2 (Paclobutrazol 2 ml/l + KNO3 20 g/l + manure 10 kg/plant + NPK Nitrophonska 1 kg/plant), and P3 (Paclobutrazol 2 ml/l + Etefon 40 ml/l + manure 10 kg/plant + NPK Nitrophonska 1 kg/plant).  The data obtained were analyzed by analysis of variance and the mean separation was carried out by orthogonal contrast test at the 5% significance level.  The results showed that the treatment of P2 (Paclobutrazol 2 ml/l + KNO3 20 g/l + manure 10 kg/plant + NPK Nitrophonska 1 kg/plant) on mangosteen plants was able to spur flowering faster with a difference of 12 days (8.70% ), and increased the total number of fruits per plant by a difference of 41 fruit (38.80%).  The P3 treatment (Paclobutrazol 2 ml/l + Etefon 40 ml/l + manure 10 kg/plant + NPK Nitrophonska 1 kg/plant), unexpectedly causing significant leaf drop 3 days after Ethephon spray, and new leaves were formed a month later.  Keywords : Ethephon, KNO3, Paclobutrazol, and mangosteen flowering